Longitudinal Bidirectional Relationships Between Maternal Depressive/Anxious Symptoms and Children's Tic Frequency in Early Adolescence - Yagi, Tomoko; Ando, Shuntaro; Usami, Satoshi; Yamasaki, Syudo; Morita, Masaya; Kiyono, Tomoki; Hayashi, Noriyuki; Endo, Kaori; Iijima, Yudai; Morimoto, Yuko; Kanata, Sho; Fujikawa, Shinya; et al. (Frontiers in Psychiatry, 2021)
Background: Previous studies have revealed an association between maternal depressive/anxious symptoms and children’s tics. However, the longitudinal relationships between these symptoms remain unclear. We examined the longitudinal relationships between maternal depressive/anxious symptoms and children’s tic frequency in early adolescence with a population-based sample. Methods: The participants consisted of 3,171 children and their mothers from the Tokyo Teen Cohort (TTC) study, a population-representative longitudinal study that was launched in Tokyo in 2012. Maternal depressive/anxious symptoms and children’s tics were examined using self-report questionnaires at the ages of 10 (time 1, T1) and 12 (time 2, T2). A cross-lagged model was used to explore the relationships between maternal depressive/anxious symptoms and children’s tic frequency. Results: Higher levels of maternal depressive/anxious symptoms at T1 were related to an increased children’s tic frequency at T2 (β = .06, p < .001). Furthermore, more frequent children’s tics at T1 were positively related to maternal depressive/anxious symptoms at T2 (β = .06, p < .001). Conclusions: These findings suggest a longitudinal bidirectional relationship between maternal depressive/anxious symptoms and children’s tic frequency in early adolescence that may exacerbate each other over time and possibly create a vicious cycle. When an early adolescent has tics, it might be important to identify and treat related maternal depressive/anxious symptoms.